1998
DOI: 10.1292/jvms.60.805
|View full text |Cite
|
Sign up to set email alerts
|

Non-invasive Blood Pressure Measurements in Cats: Clinical Significance of Hypertension Associated with Chronic Renal Failure.

Abstract: ABSTRACT. The systolic, mean and diastolic pressures as well as the heart rate were mesured using the oscillometric method, on a total of 104 cats (60 cats in the normal group, and 44 in the renal disease group) which were brought into Azabu University Animal Hospital. The blood pressure in the normal group was systolic: 115.4 ± 10.1 mmHg, mean: 96.2 ± 12.2 mmHg, and diastolic: 73.7 ± 10.7 mmHg. Although no difference in heart rate, the renal disease group showed significantly (p<0.05) higher values for systol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

5
89
1
7

Year Published

2001
2001
2020
2020

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 67 publications
(102 citation statements)
references
References 13 publications
5
89
1
7
Order By: Relevance
“…Findings in this cat were consistent with the classic form of hyperaldosteronism. The plasma aldosterone concentrations were extremely high in comparison with values in our control cats and the values found by others for healthy cats (32), and in cats with hypertension associated with chronic renal disease (13,20). Although there was some decline in aldosteroneconcentration in the iv-HDDST, the results of this test indicated autonomous (non-ACTH-dependent) hyperaldosteronism and an intact hypothalamus-pituitary-glucocorticoid axis.…”
Section: Discussionsupporting
confidence: 60%
“…Findings in this cat were consistent with the classic form of hyperaldosteronism. The plasma aldosterone concentrations were extremely high in comparison with values in our control cats and the values found by others for healthy cats (32), and in cats with hypertension associated with chronic renal disease (13,20). Although there was some decline in aldosteroneconcentration in the iv-HDDST, the results of this test indicated autonomous (non-ACTH-dependent) hyperaldosteronism and an intact hypothalamus-pituitary-glucocorticoid axis.…”
Section: Discussionsupporting
confidence: 60%
“…To date, only a limited number of studies have examined components of the RAAS in feline CKD and systemic hypertension 3, 4. In such studies, results have been contradictory but have suggested increased plasma aldosterone concentrations (PAC; pg/mL) but variable plasma renin activity (PRA; ng/mL/h).…”
mentioning
confidence: 99%
“…Causes of secondary hypertension include renoparenchymal diseases, renovascular diseases, diabetes, Cushing syndrome, primary hyperaldosteronism, pheochromocytoma and hypothyroidism and, of those, renoparenchymal disease-associated hypertension is most common in humans [24]. The mechanism of renal hypertension is thought to involve renal insufficiency-associated body fluid retention, increases in cardiac output and peripheral vessel resistance, activation of the renin-angiotensin-aldosterone (RAA) system and suppression of the kallikrein-kinin-prostaglandin system [2,3,17].A link between chronic renal failure and hypertension has been suggested in dogs and cats [1,6,12,13,22,26,27,29,30,34,[36][37][38]. Activation of the RAA system and development of hypertension in association with renal failure have been reported in cats [20,30,41].…”
mentioning
confidence: 99%
“…Activation of the RAA system and development of hypertension in association with renal failure have been reported in cats [20,30,41]. In dogs, development of hypertension following partial renal ablation has been described [10,14]; however, involvement of the RAA system has not been verified by measuring the RAA system.…”
mentioning
confidence: 99%
See 1 more Smart Citation